2014
DOI: 10.1073/pnas.1404269111
|View full text |Cite
|
Sign up to set email alerts
|

NAD + and SIRT3 control microtubule dynamics and reduce susceptibility to antimicrotubule agents

Abstract: Nicotinamide adenine dinucleotide (NAD + ) is an endogenous enzyme cofactor and cosubstrate that has effects on diverse cellular and physiologic processes, including reactive oxygen species generation, mitochondrial function, apoptosis, and axonal degeneration. A major goal is to identify the NAD + -regulated cellular pathways that may mediate these effects. Here we show that the dynamic assembly and disassembly of microtubules is markedly altered by NAD + . Furthermore, we show that the disassembly of microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…Indeed, it was recently reported that in neurons, PARP1-dependent NAD + depletion inhibits the activity of the NAD + -dependent sirtuin 1 (43), which is critical for axonogenesis and neurite growth (49)(50)(51)(52). Likewise, the dynamic modulation of microtubules, essential to growth cone motility highly depends on NAD + levels through activation of mitochondrial sirtuin 3 (53). As such, a decline in sirtuin activity due to PARP1-dependent NAD + depletion might have a profound impact on neurite growth in an inhibitory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was recently reported that in neurons, PARP1-dependent NAD + depletion inhibits the activity of the NAD + -dependent sirtuin 1 (43), which is critical for axonogenesis and neurite growth (49)(50)(51)(52). Likewise, the dynamic modulation of microtubules, essential to growth cone motility highly depends on NAD + levels through activation of mitochondrial sirtuin 3 (53). As such, a decline in sirtuin activity due to PARP1-dependent NAD + depletion might have a profound impact on neurite growth in an inhibitory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of pCMV3‐His‐SIRT3 reduces the microtubule‐destabilizing effect of VCR in leukaemia cells. Consistent with this, prior studies have revealed that transfection with a SIRT3‐expressed vector reduced the capability of vinblastine to induce disassembly of microtubule polymers in breast cancer MCF‐7 cells . Notably, Wang et al found that treatment of U937 cells with a SIRT3 inhibitor, brRESV, down‐regulated SIRT3 expression, but did not induce microtubule destabilization and mitotic arrest.…”
Section: Resultsmentioning
confidence: 53%
“…Harkcom et al found that overexpression of SIRT3 suppresses vinblastine‐induced microtubule destabilization and G 2 /M arrest. Thus, the involvement of SIRT3 in VCR cytotoxicity was analysed.…”
Section: Resultsmentioning
confidence: 99%
“…described for the tumor suppressor RITA (RBP-J and tubulin-associated protein) that interacts with HDAC6 and thereby modulates levels of K40-acetylated ïĄ-tubulin and microtubule dynamics 71 . Lastly, the NAD + -SIRT3 axis has been also implicated in the regulation of microtubule dynamics and chromosomal alignment during mitosis 32,33 . However, this function of SIRT3 is likely mitochondrial-based, given that SIRT3 is predominantly found in mitochondria ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT3 regulates, in a direct or indirect (i.e. mitochondria-dependent) manner, microtubule dynamics and chromosomal alignment during mitosis by currently unknown mechanism(s) 32,33 . SIRT4 could also play an extramitochondrial role in microtubule dynamics, given that SIRT4 interacts with Leucinerich protein 130 (LRP130) 24,34 , a multi-domain and dual-function protein that binds to the microtubule-associated protein MAP1S and integrates mitochondrial transport and the microtubule cytoskeleton in interphase 35 .…”
Section: Introductionmentioning
confidence: 99%